2023
DOI: 10.1038/s41416-023-02343-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oxidative stress adaptation in head and neck cancer cells generates slow-cyclers with decreased tumour growth in vivo

Abstract: Background Reactive oxygen species (ROS) are implicated in cancer therapy and as drivers of microenvironmental tumour cell adaptations. Medical gas plasma is a multi-ROS generating technology that has been shown effective for palliative tumour control in head and neck cancer (HNC) patients before tumour cells adapted to the oxidative stress and growth regressed fatally. Methods In a bedside-to-bench approach, we sought to explore the oxidative stress adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…The consistent outcome identified that senescence in cancer cells depressed the progression of cancer in an opposing manner. In head and neck cancer, gas plasma treatment induced cellular senescence in cancer cells through the accumulation of oxidative stress, attenuating the proliferation of cancer cells in vivo [ 62 ]. LincRNA-p21 upregulated by 1-methyl-4-phenylpyridinium could induce oxidative stress to enhance neuroblastoma cell senescence by suppressing the Wnt/β-catenin pathway, deducing the proliferation and viability of tumor cell [ 63 ].…”
Section: Oxidative Stress and Senescence In Cancer Progressionmentioning
confidence: 99%
“…The consistent outcome identified that senescence in cancer cells depressed the progression of cancer in an opposing manner. In head and neck cancer, gas plasma treatment induced cellular senescence in cancer cells through the accumulation of oxidative stress, attenuating the proliferation of cancer cells in vivo [ 62 ]. LincRNA-p21 upregulated by 1-methyl-4-phenylpyridinium could induce oxidative stress to enhance neuroblastoma cell senescence by suppressing the Wnt/β-catenin pathway, deducing the proliferation and viability of tumor cell [ 63 ].…”
Section: Oxidative Stress and Senescence In Cancer Progressionmentioning
confidence: 99%
“…In these situations, frequently repeated gas plasma exposure is amendable to control, for instance, tumor infections and/or growth to support palliation, and potentially also provide immuno-stimulation. In the clinic, however, head and neck cancer cell adaptation to gas plasma therapy-induced tumor toxicity was also observed [ 221 ], and frequent gas plasma-induced oxidative stress can select for slow-cycling tumor cells with improved stress resistance [ 292 ]. Such adaptation and reduced therapy responses, however, has been observed for most cancer therapies utilized in the clinic, and are not specific to gas plasma therapy per se .…”
Section: Quo Vadis Experimental and Clinical Gas Plasma Cancer Treatmentmentioning
confidence: 99%
“…In addition, it has been found that NTP-induced repetitive oxidative stress situations contribute to identifying potential targets for overcoming anti-cancer drug resistance [144]. However, the above studies still have some limitations, especially the short-life and weak penetration of ROS, which limit the widespread application of NTP in cancer therapy.…”
Section: Ntp Contributes To Cancer Therapy Application Of Ntp Alone I...mentioning
confidence: 99%